Biosynthesis and characterization of polyhydroxyalkanoates copolymers produced by pseudomonas putida bet001 isolated from palm oil mill effluent - Gumel, A.M.; Annuar, M.S.M.; Heidelberg, T. (Public Library of Science, 2012)
The biosynthesis and characterization of medium chain length poly-3-hydroxyalkanoates (mcl-PHA) produced by Pseudomonas putida Bet001 isolated from palm oil mill effluent was studied. The biosynthesis of mcl-PHA in this newly isolated microorganism follows a growth-associated trend. Mcl-PHA accumulation ranging from 49.7 to 68.9% on cell dry weight (CDW) basis were observed when fatty acids ranging from octanoic acid (C8:0) to oleic acid (C18:1) were used as sole carbon and energy source. Molecular weight of the polymer was found to be ranging from 55.7 to 77.7 kDa. Depending on the type of fatty acid used, the 1H NMR and GCMSMS analyses of the chiral polymer showed a composition of even and odd carbon atom chain with monomer length of C4 to C14 with C8 and C10 as the principal monomers. No unsaturated monomer was detected. Thermo-chemical analyses showed the accumulated PHA to be semi-crystalline polymer with good thermal stability, having a thermal degradation temperature (Td) of 264.6 to 318.8 (60.2) oC, melting temperature (Tm) of 43.(60.2) oC, glass transition temperature (Tg) of 21.0 (60.2) oC and apparent melting enthalpy of fusion (DHf) of 100.9 (60.1) J g21.